Electric Cars and the Resource Challenge - Henckens, Theo (Routledge, 2025)
This book is the first to fully explore the short- and long-term impact of the global electric car rollout on the supply of raw materials. The world has gone from zero to almost 1.5 billion fossil fuel cars in circulation today, contributing significantly to the global climate crisis and necessitating a total transition to electric vehicles in the coming decades. This book responds to key questions surrounding the increase of electric car usage, such as will there be sufficient resources available to permanently supply a future world population of ten billion with electric cars? What is the risk that the supply of essential raw materials will be hampered by geopolitical problems, or that mining capacity cannot be quickly scaled up? How does the switch from fossil fuel vehicles to electric cars impact the recycling of scrap cars? It contains detailed information about the material composition of electric and fossil fuel cars in relation to stocks and relative scarcity of corresponding materials in the earth's crust and estimates the ultimate annual consumption of metals based on predicted population growth. This book is an important tool for decision- makers in national ministries and international bodies, highlighting how to adopt a global long-term raw materials policy to protect the interests of future generations and global fairness. It provides necessary forecasting insight to industry leaders and specialists, policymakers, and researchers.
Keywords: Electric automobiles.; elektronické knihy; electronic books